PENERAPAN METODE PEMBELAJARAN HYPNOTEACHING DALAM MENINGKATKAN HASIL BELAJAR DI SMP NEGERI 2 KOTA MAKASSAR - Uran, Yanda Burhanurul; Syahid, Akhmad; Rosmiati; Bunyamin, Andi; Nengsih, Ratika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve student learning outcomes through the application of the Hypnoteaching learning method in Islamic Religious Education subjects in class VIII.4 of SMP Negeri 2 Makassar City. This study uses a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model which is implemented in two cycles, where each cycle consists of the planning stage, action implementation, observation, and reflection. The research subjects were 36 students of class VIII.4. Data collection techniques used observation, interviews, tests, and documentation, while data analysis was carried out descriptively quantitatively by calculating the average value and percentage of student learning completion. The results of the study show that the application of the Hypnoteaching method is able to improve student learning outcomes gradually. In the initial condition (pre-test), only 12 students (33%) achieved the Minimum Completion Criteria (KKM) of 80, while 24 students (67%) had not completed it. After the implementation of the Hypnoteaching method in Cycle I, the number of students who completed the course increased to 22 people (61%), while 14 people (39%) were still incomplete. Improvements in learning in Cycle II resulted in a significant increase, namely all 36 students (100%) successfully achieved the KKM. In addition to improving learning outcomes, the Hypnoteaching method is also able to increase motivation, activeness, attention, self-confidence, and participation of students during the learning process. Thus, it can be concluded that the implementation of the Hypnoteaching method is effective in improving student learning outcomes in Islamic Religious Education subjects in class VIII.4 of SMP Negeri 2 Makassar City and is worthy of being used as an alternative learning method to create a more active, enjoyable, and meaningful learning process.